2004
DOI: 10.2337/diabetes.53.8.1966
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Hypocaloric Diets on Protein Secretion From Adipose Tissue of Obese Women

Abstract: Little is known about common factors (e.g., macronutrients and energy supply) regulating the protein secretory function of adipose tissue. We therefore compared the effects of randomly assigned 10-week hypoenergetic (؊600 kcal/day) diets with moderate-fat/moderate-carbohydrate or low-fat/high-carbohydrate content on circulating levels and production of proteins (using radioimmunoassays and enzyme-linked immunosorbent assays) from subcutaneous adipose tissue in 40 obese but otherwise healthy women. Similar resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
157
2
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(171 citation statements)
references
References 53 publications
9
157
2
3
Order By: Relevance
“…This decrease in IL8 expression was closely associated to the LCD-induced reduction in body fat mass, suggesting that it could be a good indicator of variations in body fat percentage. This finding supports previous work indicating a upregulation of IL8 gene expression in preadipocytes of obese subjects (Nair et al, 2005), as well as studies that show a decrease in the adipose tissue IL8 secretion in humans treated following a hypocaloric diets (Arvidsson et al, 2004).…”
Section: Crujeiras Et Al 258supporting
confidence: 81%
“…This decrease in IL8 expression was closely associated to the LCD-induced reduction in body fat mass, suggesting that it could be a good indicator of variations in body fat percentage. This finding supports previous work indicating a upregulation of IL8 gene expression in preadipocytes of obese subjects (Nair et al, 2005), as well as studies that show a decrease in the adipose tissue IL8 secretion in humans treated following a hypocaloric diets (Arvidsson et al, 2004).…”
Section: Crujeiras Et Al 258supporting
confidence: 81%
“…Indeed the risk of death from multiorgan failure was shown to be greater in obese patients than in patients with normal weight (13,14) . A study on obese women clearly showed that a reduction in adipose tissue mass, achieved by consuming 2520 kJ/day for 10 weeks, substantially reduced the ability of adipose tissue to produce TNFa, IL-6, IL-8 and leptin (15) .…”
Section: Influence Of Adipose Tissue Mass On Inflammatory Stressmentioning
confidence: 99%
“…28,30 Glycerol (lipolysis index) was determined by bioluminescence assay. 31 Owing to the limited amount of samples, it was not possible to measure all compounds in all subjects.…”
Section: Measurement Of Adiponectin Glycerol Tnfa and Il-6 Media Inmentioning
confidence: 99%
“…Methodological experiments validated this incubation system for studies of protein release in vitro, because secreted proteins display a linear increase with time during incubation. 28 In clinical needle biopsy experiments conducted on 24 obese and 22 lean subjects, 300 mg tissue pieces were incubated as described above for 2 h. The amount of protein secreted into the incubation medium was determined and related to tissue weight or number of fat cells, as described previously. 28 In brief, after weighing, incubated tissues were subjected to organic extraction and lipid content was determined.…”
Section: Secretion Of Trap From the Human Adipose Tissuementioning
confidence: 99%
See 1 more Smart Citation